Exploiting symmetry in SAT-based boolean matching for heterogeneous FPGA technology mapping - Yu Hu; Shih, V.; Majumdar, R.; Lei He (2007 IEEE/ACM International Conference on Computer-Aided Design, 2007)
The Boolean matching problem is a key procedure in technology mapping for heterogeneous field programmable gate arrays (FPGA), and SAT-based Boolean matching (SAT-BM) provides a highly flexible solution for various FPGA architectures. However, the computational complexity of state-of-the-art SAT-BM prohibits its application practically. In this paper we propose an efficient SAT-BM algorithm by exploring function and architectural symmetries. While the most recent work obtained up to 13times speedup, we achieve up to 200times speedup, when both are compared to the original SAT-BM algorithm.